ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN PADA IBIS STYLES BALI - I Gede Witayasa; I Gede Dedik Bayu Ariawan (Majalah Ilmiah Widyacakra, 2020)
ABSTRACTThis research aimed to analyze the influence of the tourist satisfaction on service quality atIbis Styles Bali. The sample of this research is 78 respondents. The Data sources used in thisresearch are primary and secondary data. Data is analyzed using path analysis that isassisted with SPSS for Windows version 22. Data collection method in this research usinginterview method, by means of questionnaires. The analytical technique used is ImportancePerformance Analysis (Cartesius Diagram). This diagram can be used to identify the servicesignificance and customer satisfaction level on service quality of a company. Results ofImportance Performance Analysis (Cartesius Diagram) known that the good service andready to help (indicator 8) is located at Quadrant A, it means that the indicator 8 need to bepriority because considered important for the customers. Polite (indicator 12), attention(indicator 16) and customer needs (indicator 17) are located at Quadrant C, it means that theindicators are less satisfying and considered important to the customers. The clean and goodperformance of employee (indicator 4) is located at Quadrant D, it means that the indicator 4is less important to the customers. Indicator the building and interior are nice and attractive(indicator 1), The cleanliness and comfort hotel (indicator 2), the hotel facilities are complete(indicator 3), service time (indicator 5), the good promised service (indicator 6), The goodcheck-in and check-out procedures (indicator 7), Quick response to the problems (indicator9), Quick response to the complaints (indicator 10), the clear information sharing (indicator11), the employees knowledge of public area and private areas (indicator 13), effectivecommunication (indicator 14), and responsible for security and comfort (indicator 15) arelocated at Quadrant B, it means that they are satisfying and considered important for thecustomers of quality at Ibis Style Hotel Bali.